Study of insulin resistance, cortisol hormone and some biochemical parameters in Iraqi type 2 diabetic patients - Al-Fayyadh, Mohanad Salam Majeed; Kefah H. Ismael; Ali J.R.Al-Saady (University of Thi-Qar Journal of Science, 2023)
The most prevalent type of diabetes disease is type 2. It resulted through cells' failure for recognizing and responding to insulin, which can increase the risk of this disease  if improperly managed. This work seeks to assess  few biochemical variables connected to glycemic index in people  with type 2 diabetes (T2D). In this study, certain biochemical markers were taken from 37 patients with  diabetes mellitus (DM). In the current study,  lipid profile, kidney function, insulin, glycated hemoglobin (HbA1c), fasting blood sugar (FBS), uric acid, insulin resistance (HOMA-IR) and cortisol hormone were measured. The blood serum of the 37 patients were taken from diabetic center in Yarmouk hospital and 27 control sample were taken from healthy people  in the University of Baghdad.  The ages for healthy and unhealthy patients were (19 to 47 ) years old. The results showed that, diabetic participants had higher HbA1c, FBS, HOMA-IR, cortisol, urea, uric acid, lipid profile, and creatinine levels comparing to the control samples at P≤0.05. We concluded from this study, abnormally elevated levels of serum cortisol, FBS, HbA1c, and insulin. Increasing  HOMA-IR indicated  that IR is a risk factor for T2DM development. This work revealed a  relationship between T2DM and kidney function parameters. It was found that patients with T2D having higher levels of creatinine and urea.